2020
DOI: 10.1177/0897190020953024
|View full text |Cite
|
Sign up to set email alerts
|

Non-Lactulose Medication Therapies for the Management of Hepatic Encephalopathy: A Literature Review

Abstract: Objective: The most appropriate medication regimen to mitigate the consequences hepatic encephalopathy remains inconclusive. This review seeks to serve as a reference for clinicians to help guide therapy decisions with regard to hepatic encephalopathy. Methods: A comprehensive literature review between August 2018 and April 2019 was accomplished with the assistance of a medical librarian. Sources of literature review include PubMed, MEDLINE, SCOPUS, ProQuest Central, CINAHL, and ProQuest Dissertations. The aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…In one study, rifaximin was found effective in 22.1% cases of hepatic encephalopathy. 12 While according to another study 13 , metronidazole is effective in 78% patients.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In one study, rifaximin was found effective in 22.1% cases of hepatic encephalopathy. 12 While according to another study 13 , metronidazole is effective in 78% patients.…”
Section: Discussionmentioning
confidence: 98%
“…14 The adjustment of disaccharide dose in order to get two to three bowel movements per day often leads to side effects like nausea, vomiting, flatulence and poor drug compliance. 13 Oral antibiotics such as neomycin, vancomycin or paromomycin are more useful than disaccharides and have less side effects, but have a risk of toxicity. 13,16 Due to this risk of toxicity, these agents are not commonly used in clinical practice now a days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rifaximin is a systematically studied antibiotic for the treatment of HE which has minimal systemic absorption, a subtle adverse effect profile, and a low risk for bacterial resistance due its gut-selective nature. The efficacy and safety of this medication makes rifaximin an important therapeutic tool for the management of HE because it alleviates endotoxemia and improves cognition 57 .…”
Section: Treatments That Reduce Peripheral Inflammationmentioning
confidence: 99%